Sistem Pengelolaan Arsip Debitur di PT Bank Negara Indonesia (Persero) Tbk. Kantor Cabang Utama Padang - Hamdani, Revi; Marlini, Marlini (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2016)
This paper discussed about the debtor records management system in PT. Bank Negara Indonesia (Persero) Tbk. Main Branch Office Padang. The purposes of this paper is (1) to describe how the debtor records management system in PT. Bank Negara Indonesia (Persero) Tbk. Main Branch Office Padang; (2) to describe some obstacles encountered by PT. Bank Negara Indonesia (Persero) Tbk. Main Branch Office Padang in the process of records management debtor; (3) to describe the efforts made to overcome the obstacles in the process of records management debtor in PT. Bank Negara Indonesia (Persero) Tbk. Main Branch Office Padang. Data were collected through observation, interviews, and intership activity. Based on the research results, we can conclude: First, archive storage systems debtors in PT. Bank Negara Indonesia (Persero) Tbk. Main Branch Office Padang using alphabetic system. Second, obstacles which are encountered, are (1) improper storage system; (2) infrastructure and maintenance of archive storage space is not optimal; (3) the absence of professional archivists. Third, the efforts which are being made to overcome the obstacles, are (1) improve storage system whch is used; (2) optimize storage space and archives maintenance, (3) the provision of professional archivists and providing training or education about filing for employees.Keyword: debtor; records; management